2015
DOI: 10.1093/cvr/cvv263
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hedgehog signalling-induced endothelial dysfunction is sufficient to induce neuropathy: implication in diabetes

Abstract: The present work demonstrates the critical role of Dhh in maintaining blood nerve barrier integrity and demonstrates for the first time that endothelial dysfunction is sufficient to induce neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 50 publications
2
45
2
Order By: Relevance
“…To confirm that endothelial Dhh and ectopic N-Shh induce opposite effects on ECs, we compared their effect on endothelial barrier integrity. Consistent, with previous investigations 17,27 , expression of both Cdh5 and Cldn5 was significantly diminished at the BBB of Dhh ECKO mice compared to littermate controls (Figure 2A-D). This was associated with fibrinogen and albumin extravasation (Figure 2A-B, E-F) demonstrating abnormal BBB permeability.…”
Section: Endothelial Dhh Promotes Bbb Integrity While Ectopic Adminissupporting
confidence: 92%
“…To confirm that endothelial Dhh and ectopic N-Shh induce opposite effects on ECs, we compared their effect on endothelial barrier integrity. Consistent, with previous investigations 17,27 , expression of both Cdh5 and Cldn5 was significantly diminished at the BBB of Dhh ECKO mice compared to littermate controls (Figure 2A-D). This was associated with fibrinogen and albumin extravasation (Figure 2A-B, E-F) demonstrating abnormal BBB permeability.…”
Section: Endothelial Dhh Promotes Bbb Integrity While Ectopic Adminissupporting
confidence: 92%
“…Nevertheless, many rodent models of diabetes exhibit indicators of Schwann cell dysfunction, including reduced expression of myelin-associated proteins 47 and Schwann cell-derived trophic factors, such as CNTF 19 and desert hedgehog 20,48 . These perturbations have the potential to affect both neuronal 49 and vascular 48 function, and changes in CNTF expression are prevented by aldose reductase inhibition 50 . In addition, studies in cultured Schwann cells have suggested that increased flux through the polyol pathway drives Schwann cells towards an immature phenotype 51 .…”
Section: Polyneuropathy Mononeuropathiesmentioning
confidence: 99%
“…This resulted in increased local vascular permeability, local immunocytes infiltration, and neuropathic-like behavior development (mechanical allodynia) in CCI-injured rats. 4 , 5 , 9 Nevertheless, neither the preemptive inhibition of TLR4 signaling nor the preemptive activation of Hedgehog signaling in healthy nerves could prevent the molecular, vascular, and behavioral changes resulting from CCI, suggesting the possibility of other players in this pathological context.…”
Section: Introductionmentioning
confidence: 99%